PROXIMATE ASSAY AND AMINO ACIDS PROFILE OF SEA CUCUMBER (Stichopus vastus) FLOUR WITH DIFFERENT HEATING TREATMENTS - Mohamad Irvan Ibrahim; Mery Sukmiwati; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Stichopus vastusis one type of sea cucumber that hasn’t been optimally utilized, therefore this study was aimed to determine the proximate values and amino acids profile of sea cucumber (Stichopus vastus) flour with different heating treatments. The method used in this study was the experimental method, with a different processed of heating (boiled and steamed). The results showed that the sea cucumber flour produced by boiling process had a water, ash, fat, protein and carbohydrate content was 11.53%, 10.76%, 2.22%, 57.86%, and 14.00%, respectively. Meanwhile the sea cucumber flour produced by steaming process was 11.69%, 13.79%, 2.17%, 61.49% and 14.49%, respectively.Total amino acids in sea cucumber flour with boiling and steaming process were 50.34% and 52.95%, respectively, with the highest amino acid content of each treatment was glycine and the lowest content of amino acid was methionine. Keywords: amino acid, Stichopus vastus, sea cucumber flour, heating